Analisis Kapasitas Tingkat Pelayanan dan Kinerja Ruas Jalan Inspeksi Kalimalang - Alfira Fadilla Yasmin; Danny Setiawan (Institut Transportasi dan Logistik Trisakti, 2021)
Inspeksi Kalimalang Street is the street connecting to industrial areas of Jababeka, MM2000, EJIP, Delta Mas and other industrial areas. According to Detik Finance (2017), 2.125 factory units of 25 countries locate in area of Bekasi District, Because mobility of in-out industrial vehicles transporting raw materials or products from and to export destinations are high, vehicles frequently collect in Inspeksi Kalimalang Street. This study aims at analyzing capacity of service level and performance of Inspeksi Kalimalang Street and analyzing comparison of line change based on (MKJI 1997). The results of analysis indicate that street condition with lane (2/2 UD) of segment one had service level F with mean capacity value (C)=2674,136 smp/hour in west direction and 2728,394 smp/hour in east direction. Mean saturation degree value of segment one (DS) = 0,821 in west direction and 0,776 in east direction > 0,75 as MKJI recommended. Whereas the result of lane widening comparison into (4/2 D) in segment one had service level D, where mean capacity value of segment one (C)=3130,807 smp/hour in west direction and 3265,890 smp/hour in east direction. Mean saturation degree value of segment one (DS) = 0,700 in west direction and 0,647 in east direction < 0,75 as MKJI 1997 recommended.